RhoA and Rac1 GTPases play major and differential roles in stromal cell-derived factor-1-induced cell adhesion and chemotaxis in multiple myeloma - Azab, Abdel Kareem; Azab, Feda; Blotta, Simona; Pitsillides, Costas; Thompson, Brian D.; Runnels, Judith M.; Roccaro, Aldo Maria; Ngo, Hai T.; Melhem, Molly R.; Sacco, Antonio; Jia, Xiaoying; Anderson, Kenneth Carl; et al. (My University, 2009)
The interaction of multiple myeloma (MM) cells with the bone marrow (BM) milieu plays a crucial role in MM pathogenesis. Stromal cell–derived factor-1 (SDF1) regulates homing of MM cells to the BM. In this study, we examined the role of RhoA and Rac1 GTPases in SDF1-induced adhesion and chemotaxis of MM. We found that both RhoA and Rac1 play key roles in SDF1-induced adhesion of MM cells to BM stromal cells, whereas RhoA was involved in chemotaxis and motility. Furthermore, both ROCK and Rac1 inhibitors reduced SDF1-induced polymerization of actin and activation of LIMK, SRC, FAK, and cofilin. Moreover, RhoA and Rac1 reduced homing of MM cells to BM niches. In conclusion, we characterized the role of RhoA and Rac1 GTPases in SDF1-induced adhesion, chemotaxis, and homing of MM cells to the BM, providing the framework for targeting RhoA and Rac1 GTPases as novel MM therapy
Keywords: Cell adhesion; Multiple myeloma; Chemotaxis; Mice; Animal experimentation; Cells; Cytoskeleton